Thermal Decomposition Studies of Lanthanide(III) Complexes of EDTA - S. Kumar, Asha; Indrasenan, P. (Asian Journal of Chemistry, 2010)
Thermal decomposition studies of lanthanide(III) complexes of EDTA in nitrogen and air atmospheres are studied using simultaneous TG-DTA. The phenomenological as well as the kinetic aspects of thermal decomposition is described. Based on the observed experimental results, a general mechanism is also proposed. The stability of the complexes in both the atmospheres is also compared.